Effects of Music Aerobic Exercise on Depression and Brain-Derived Neurotrophic Factor Levels in Community Dwelling Women. (14th May 2015) - Yeh, Shu-Hui; Lin, Li-Wei; Chuang, Yu Kuan; Liu, Cheng-Ling; Tsai, Lu-Jen; Tsuei, Feng-Shiou; Lee, Ming-Tsung; Hsiao, Chiu-Yueh; Yang, Kuender D.
Abstract : A randomized clinical trial was utilized to compare the improvement of depression and brain-derived neurotrophic factor (BDNF) levels between community women with and without music aerobic exercise (MAE) for 12 weeks. The MAE group involved 47 eligible participants, whereas the comparison group had 59 participants. No significant differences were recorded in the demographic characteristics between the participants in the MAE group and the comparison group. Forty-one participants in the MAE group and 26 in the comparison group completed a pre- and posttest. The MAE group displayed significant improvement in depression scores ( p = 0.016), decreased depression symptoms in crying ( p = 0.03), appetite ( p = 0.006), and fatigue ( p = 0.011). The BDNF levels of the participants significantly increased after the 12-week MAE ( p = 0.042). The parallel comparison group revealed no significant changes in depression scores or BDNF levels. In summary, the 12-week MAE had a significant impact on the enhancement of BDNF levels and improvement of depression symptoms. Middle-aged community women are encouraged to exercise moderately to improve their depression symptoms and BDNF levels.